Algal Growth at Environmentally Relevant Concentrations of Suspended Solids: Implications for Microplastic Hazard Assessment - Gorokhova, Elena; Ek, Karin; Reichelt, Sophia (Frontiers in Environmental Science, 2020)
Hazard assessment of microplastic is challenging because standard toxicity testing is targeting soluble (at least partially) chemicals. Adverse effects can occur when test organisms are exposed to turbid environments in the presence of various particulate matter (PM), both natural, such as clay and cellulose, and anthropogenic, such as microplastic. It is, therefore, relevant to compare responses to PM exposure between the microplastic and other suspended solids present at ecologically relevant concentrations. This comparison is possible when reference materials are included in the testing of microplastic hazard potential. Here, we evaluated growth inhibition in unicellular alga Raphidocelis subcapitata exposed to different PM (microplastic, kaolin, and cellulose; 10, 100, and 1000 mg/L); algae without added solids were used as a control. Also, aggregate formation in the exposure systems was analyzed using particle size distribution data. At 10 and 100 mg/L, no adverse growth effects were observed in any treatments; moreover, algal growth was significantly stimulated in kaolin and cellulose treatments compared to the control. However, at 1000 mg/L, all tested materials exerted growth inhibition, with no significant differences among the materials. Comparing particle size distributions across the treatments showed that both PM concentration and size of the particle aggregates were significant growth predictors for all materials tested. Therefore, at high concentrations, both natural and anthropogenic materials have a similar capacity to cause growth inhibition. Linking effects in unicellular organisms to microplastic fragments remains a challenge since plastics incorporate chemicals that may leach and elicit specific effects relative to the particulates. The use of reference materials in hazard assessment of plastic litter is needed to delineate these effects.